2012
DOI: 10.4104/pcrj.2012.00017
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining outcome data on asthma management: the UK National Review of Asthma Deaths

Mark L Levy

Abstract: Preventable factors related to asthma deaths have been known for over 50 years.1-3 These relate to clinical management -both acute and chronic -and patients' own understanding and care of their condition. With excellent evidence-based UK guidelines (http://www.sign.ac.uk/pdf/ sign101.pdf) and an international strategy (http://www.ginasthma.org/) for management of asthma, it is surprising that preventable factors are still identified in asthma deaths in the UK.The study by Anagnostou et al. 4 (published onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It should investigate deaths across all age groups, the circumstances surrounding the death as well as the management of fatal attacks and the quality of care in the preceding 12 months such as that currently being undertaken in the UK. 30 and graphs. The initial draft of the manuscript was prepared by DG and then circulated repeatedly among all authors for critical revision.…”
Section: Future Researchmentioning
confidence: 99%
“…It should investigate deaths across all age groups, the circumstances surrounding the death as well as the management of fatal attacks and the quality of care in the preceding 12 months such as that currently being undertaken in the UK. 30 and graphs. The initial draft of the manuscript was prepared by DG and then circulated repeatedly among all authors for critical revision.…”
Section: Future Researchmentioning
confidence: 99%
“…The systemic barriers to the use of AHPs are not isolated to supporting Autistic patients; the UK National Review of Asthma Deaths identified that 70% of the children who died did not have a written asthma management plan, despite the known mortality risk in childhood asthma [ 38 ]. Accordingly, before recommending them as a tool that will reduce health inequality, healthcare systems must be redesigned in such a way that these health passport type tools become a valuable resource, rather than a tokenistic low-cost intervention.…”
Section: Discussionmentioning
confidence: 99%